2011
DOI: 10.1016/j.jmii.2011.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing and in vitro fluconazole susceptibility of Candida species isolated from diabetic and nondiabetic women with vulvovaginal candidiasis in India

Abstract: Ninety-five percent of the C albicans isolates analyzed were different and genetically unrelated. The analysis of the AP-PCR DNA banding pattern of C glabrata isolates showed that it resembled genotype "A". The Candida isolates were found to be susceptible to fluconazole, with minimum inhibitory concentrations ranging from 0.5 μg/mL to 8 μg/mL. This correlates with the use of fluconazole as a first-choice antifungal for treating VVC in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…At the same time, people of different educational backgrounds could have the same avenue to obtain the massive information related to health-care through the Internet. Studies [ 17 19 ] have showed that diabetes mellitus, especially uncontrolled diabetes mellitus, was conducive to the occurrence of VVC. The current study could not elute the relation between diabetes mellitus and VVC because of lack of data on diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, people of different educational backgrounds could have the same avenue to obtain the massive information related to health-care through the Internet. Studies [ 17 19 ] have showed that diabetes mellitus, especially uncontrolled diabetes mellitus, was conducive to the occurrence of VVC. The current study could not elute the relation between diabetes mellitus and VVC because of lack of data on diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“… 10 In other studies, similar results were obtained, reporting that VVC species strains of genus Candida presented resistance and also a high frequency of SDD for nystatin and sensitivity to others tested drugs. 26 , 35 , 43 …”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have described associations between DM and VVC, colonization and RVVC, in different countries. 6 , 10 This is very worrisome because VVC afflicts millions of both non-diabetic and diabetic women, causing great discomfort and interfering with sexual and affective relations. 2 , 3 Uncontrolled DM causes metabolic alterations, such as increased levels of glycogen, which can significantly increase colonization and infection by Candida.…”
Section: Discussionmentioning
confidence: 99%